Nasoseptal Flap for Skull Base Reconstruction in Children - Ben-Ari, Oded; Wengier, Anat; Ringel, Barak; Carmel Neiderman, Narin N.; Ram, Zvi; Margalit, Nevo; Fliss, Dan M.; Abergel, Avraham (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objective The endoscopic endonasal approach is being increasingly used for the resection and reconstruction of anterior skull base (ASB) lesions. Vascularized nasoseptal flaps (NSF) have become the workhorse for the reconstruction of ASB defects, resulting in a significant decrease in the incidence of cerebrospinal fluid (CSF) leaks. The objective of this study was to investigate the efficacy and safety of NSF in children.Methods This is a retrospective analysis of the medical records of all patients under the age of 18 years who underwent endoscopic repair of ASB lesions with the use of NSF at our tertiary medical center between 1/2011 and 8/2016.Results Twelve children underwent ASB defect repair for both benign and malignant neoplasms using the endoscopic endonasal NSF technique. Four children had previously undergone ASB surgery. The male-to-female ratio was 1:1, the average age was 12.3 years, the average hospitalization time was 8.3 days, and the maximum follow-up period was 24 months, during which craniofacial growth appeared to be unimpaired. A lumbar drain was used postoperatively in six cases. Crust formation and synechia were observed in two cases. There was one case of a major long-term complication (a CSF leak followed by meningitis).Conclusions Endoscopic endonasal NSF was both an effective and a safe technique for ASB defect reconstruction in 12 children for both benign and malignant neoplasms. It had a high success rate and a low complication rate. No apparent negative influence on craniofacial growth was observed in our series.
Keywords: nasoseptal flap; anterior skull base; endoscopic endonasal approach; reconstruction; children; pediatric; craniofacial growth; CSF leak